Kualitas Interaksi Multi Arah pada Pembelajaran Berbantuan Edmodo untuk Mata Pelajaran Komputer dan Jaringan Dasar (Studi pada Kelas X Jurusan Teknik Komputer dan Jaringan SMK Negeri 3 Malang) - Intan Kikis Sahara; Satrio Hadi Wijoyo; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Learning is a combination of teaching and study activities that involve an active interaction between the teacher and students so that the specified goals are achieved. However, there are problems when implementing learning in class X of the Department of Computer and Network Engineering at Vocational High School 3 of Malang that is the lack of quality of multi-direction interaction caused by the limited frequency of time teachers teach directly in the classroom and students passively ask questions during learning. The population in this research were all grade X students the Department of Computer and Network Engineering in the 2018/2019 academic year who were attending Computer and Basic Networking subjects with a total of 71 students. The sampling technique used in this research is the saturated sampling technique because all members of population are made into a research sample consisting of 35 students of class X TKJ 1 and 36 students of class X TKJ 2. In this research using data collection techniques in the form of observation, interviews, and questionnaires. This research compares between conventional learning models and blended learning models with Edmodo aims to improve the quality of multi-directional interaction. The type of weak experimental research using a static-group pretest-posttest design was used in this research. Based on the results of hypothesis testing, the researchers found that there was a significant difference in the quality of multi-direction interaction between the blended learning classes with Edmodo compared to the conventional learning classes based on evidence from the results of the t-test.